2021
DOI: 10.21037/atm-20-1604
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic significance of chemokines CCL11 and CCL5 modulated by low-density lipoprotein cholesterol in colon cancer patients with normal body mass index

Abstract: Background: Many studies have shown an elevated level of cholesterol in colon tumors as compared to normal tissue. Obesity and high low-density lipoprotein cholesterol (LDL-C) are known risk factors for colon cancer. However, the role of LDL-C in colon cancer patients with normal body mass index (BMI) remains elusive.Methods: Levels of serum cholesterol and oxysterols were quantified by ultra-performance liquid chromatography-tandem mass spectrometer (UPLC-MS/MS) from 129 individuals with normal BMI, including… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 41 publications
(45 reference statements)
0
5
0
Order By: Relevance
“…Other factors including calprotectin, a sensitive marker for mucosal inflammation of the intestine [ 50 ] or lactoferrin, a first-line defense protein for protection against microbial infections [ 51 ] were increased in our patients with obesity and T2D. Reportedly, pro-inflammatory chemokines exhibit important roles in the development of intestinal diseases even in colon carcinogenesis [ 52 , 53 ]. An aberrant microbiota has been shown to induce the epithelial expression of CCL5, promoting a spontaneous and exaggerated autoinflammatory response [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…Other factors including calprotectin, a sensitive marker for mucosal inflammation of the intestine [ 50 ] or lactoferrin, a first-line defense protein for protection against microbial infections [ 51 ] were increased in our patients with obesity and T2D. Reportedly, pro-inflammatory chemokines exhibit important roles in the development of intestinal diseases even in colon carcinogenesis [ 52 , 53 ]. An aberrant microbiota has been shown to induce the epithelial expression of CCL5, promoting a spontaneous and exaggerated autoinflammatory response [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…As a consequence, the increased plasma LDL-C levels could cause hypercholesterolemia that is associated with tumor cell growth 37 . It has been reported that LDL-C could potentiate colon cancer cell resistance to glucose-deprivation 38 . In our study, we found that recombinant Pcsk9 protein could decrease the protein level of Ldlr (Supplementary Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Our results showed that CTLA4 expression is related to the tumor infiltration characteristics of multiple immune cell types. CCL11, a neutrophil-related chemokine, exerts a chemotactic effect on eosinophils by interacting with CXCR3 and CCR5 ( Wang et al, 2021b ), which was found to be a potential prognostic signature for TNM stage II CC patients ( Liu et al, 2021b ). NIN is essential for the construction of the centrosome and helps regulate cell migration and polarity ( Goldspink et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%